The effect of low-level diode laser on COX-2 gene expression in chronic periodontitis patients - Pesevska S; Gjorgoski I; Ivanovski K; Soldatos N; Angelov N (Springer Science and Business Media LLC, 2017)
Adjunctive treatments to scaling and root planing (SRP) such as lasers, have been utilized in the treatment of chronic periodontitis, mainly aiming to suppress and eliminate the bacteria, as well as enhancing the healing response. Eighty gingival papilla biopsy samples were obtained from 60 patients diagnosed with chronic advanced periodontitis; randomly assigned to three treatment groups (n = 20), as well as 20 subjects with no periodontal disease [group A]. Group B received SRP on a single quadrant/day for four consecutive days. On day 5, all quadrants were rescaled. Groups C and D received the same treatment as group B plus laser application with the low-level diode laser (630-670 nm, 1.875 J/cm2) for five and ten consecutive days, respectively. Papilla biopsies were obtained from subjects and evaluated by RT-PCR for expression of COX-2. The values in the control group were 0.028 0.014 and baseline values for the examined groups were 0.16 0.18. Significantly decreased level of COX-2 expression for groups C and D was found after treatment, while lowest average expression was found in the group that had the 10 laser treatments supplemental to SRP (0,035 0,014). The results of this study show suppression of COX-2 in gingival tissue after low-level laser treatment as adjunct to SRP.